Case Report: Guillain–Barré syndrome with three episodes and literature review - Wang, Ying; Zhao, Chunmei; Chen, Rong; Ma, Zeli; Tian, Nan; Li, Xuan; Xu, Xianrui; Liu, Qiang; Li, Yajun; She, Fenkui; Mu, Fenglin; Zhang, Qing (Frontiers in Immunology, 2025)
Guillain–Barré syndrome (GBS) is an autoimmune-mediated peripheral neuropathy that is usually monophasic, but recurrence occurs in 2%–5% of cases, termed recurrent Guillain–Barré syndrome (RGBS). We report the case of a 49-year-old male patient who experienced three episodes of bilateral lower extremity numbness and weakness, each progressing to its nadir within 4 weeks. The first episode was additionally characterized by bilateral upper extremity weakness and dyspnea, while the first two episodes were accompanied by numbness in the fingertips of both hands. Electromyography (EMG) revealed severe axonal damage with concomitant demyelination. Anti-sulfatide IgG antibodies were detected during the third episode. After excluding other demyelinating disorders, a definitive diagnosis of GBS was established, and the symptoms were nearly completely resolved following treatment with intravenous immunoglobulin (IVIG).